Can augmented reality satisfy consumers' need for touch? - Shirin Gatter; Verena Hüttl-Maack; Philipp A. Rauschnabel (Psychology & Marketing, 2021)
Consumers with a high autotelic need for touch tend to experience deprivation because they cannot touch products while shopping online. Augmented reality (AR) in retail allows consumers to explore products virtually as if they were present in the physical environment, except the fact that they are not touchable. This study investigates whether AR can compensate for this lack of touch or whether, on the contrary, these consumers are skeptical because they crave even more real haptic input. The results of four studies consistently show that consumers' autotelic need for touch is associated with benefits that positively impact various managerially relevant outcomes such as store and product attitudes or purchase intentions. However, the results also point to differences between expected and experienced hedonic and utilitarian benefits along the customer journey. Hedonic benefits prevail when consumers with a high need for touch actually experience AR, while they instead expect utilitarian benefits. The findings contribute to the AR marketing and online retailing literature by demonstrating that AR features can mimic touchable features of products. They also highlight the practical benefits of AR as a powerful tool in digital marketing.
Keywords: 650; augmented reality; autotelic need for touch; hedonic benefits; expected gratifications; marketing; retail; obtained gratifications; technology acceptance; utilitarian benefits